INFLUENCE OF QUALITATIVE TRAITS ON ZOOMETRIC CHARACTERISTICS OF DONKEYS IN NORTH WEST NIGERIA - John, P. A.; Iyiola-Tunji, A. O. (FUDMA JOURNAL OF SCIENCES, 2023)
Qualitative and zoometrical traits were used to determine the relationship among Red (Auraki), Black (Duni), White (Fari), Brown (Idabari) and Brown-white (Idabari-fari) donkeys at different ages. A total of 700 donkeys were used for the study. Zoometric measures taken were body weight, head length, head width, ear length, neck length, neck circumference, shoulder width, height at withers, heart girth, body length and tail length. The qualitative data were collected on hair type, skin colour, skin type, coat colour pattern, tail shape, eye colour and head profile. Data obtained were subjected to statistical analysis system (SAS) to determine the distribution of phenotypic traits. Analysis of variance were used to determine the effect of various qualitative factors on zoometric indices. Significant variations were observed between qualitative (P<0.01) and zoometric (P<0.01) traits of donkeys. The results of the study showed that the short-smooth hair type, brown coat colour, thick skin type, solid coat colour pattern, high-set tail shape, brown eye colour and straight head profile were preponderant in the studied population. The adult body size measures of donkeys in Northwestern Nigeria were body weight (149.3kg), Body length (108.6cm), Heart girth (118.0cm), Height at withers (111.6cm), Shoulder width (24.0cm), Neck circumference (63.0cm), Neck length (52.0cm), Head length (47.4cm), Head width (16.0cm), Ear length (26.0cm) and Tail length (60.0cm). The qualitative and zoometric differences existed among the observed strains of donkeys in the Northwestern Nigeria. Further studies should be carried out for determination of diversity that exists among strains of donkeys in Nigeria